Effect of Fluorouracil, Leucovorin, and Oxaliplatin With or Without Onartuzumab in HER2-Negative, MET-Positive Gastroesophageal Adenocarcinoma: The METGastric Randomized Clinical Trial - Shah, Manish A. (JAMA Oncol, 2016)
IMPORTANCE: Dysregulation of the mesenchymal-epithelial transition (MET) signaling pathway is associated with poor prognosis in gastroesophageal adenocarcinoma (GEC). We report results of METGastric, a phase 3 trial of the MET inhibitor onartuzumab plus standard first-line chemotherapy for human epidermal growth factor receptor 2 (HER2)-negative, MET-positive, advanced GEC. OBJECTIVE: To determine whether the addition of onartuzumab to first-line fluorouracil, leucovorin, and oxaliplatin (mFOLFOX6) improves efficacy compared with mFOLFOX6 plus placebo in HER2-negative, MET-positive GEC. DESIGN, SETTING, AND PARTICIPANTS: Randomized, double-blind, multicenter trial conducted from November 2012 to March 2014. Patients were 18 years or older with an adenocarcinoma of the stomach or gastroesophageal junction with metastatic disease not amenable for curative therapy. Tumor samples were centrally tested for MET expression using Ventana anti-Total c-MET (SP44) rabbit monoclonal antibody, HER2 status, and Lauren histologic subtype. MET-positive tumors were defined as at least 50% of tumor cells showing weak, moderate, and/or strong staining intensity (MET 1+/2+/3+, respectively) by immunohistochemistry. INTERVENTIONS: Patients with HER2-negative, MET-positive GEC were enrolled and randomized 1:1 to receive mFOLFOX6 with or without onartuzumab (10 mg/kg). MAIN OUTCOMES AND MEASURES: Co–primary end points: overall survival in the intent-to-treat (ITT) population and in patients with MET 2+/3+ GEC. Secondary end points: progression-free survival (PFS), overall response rate (ORR), and safety. RESULTS: Enrollment was stopped early due to sponsor decision, which was agreed with an independent data monitoring committee. At the data cutoff (April 25, 2014) there were 562 patients in the ITT population (n = 283 placebo plus mFOLFOX6 [median age, 58 y; 65% male]; n = 279 onartuzumab plus mFOLFOX6 [median age, 60 y; 67% male]); 109 (38.5%) and 105 (37.6%) of the ITT population were MET 2+/3+, respectively. Addition of onartuzumab to mFOLFOX6 did not significantly improve OS, PFS, or ORR vs placebo plus mFOLFOX6 in the ITT (OS hazard ratio [HR], 0.82; 95% CI, 0.59-1.15; P = .24; PFS HR, 0.90; 95% CI, 0.71-1.16; P = .43; ORR, 46.1% vs 40.6%) or MET 2+/3+ populations (OS HR, 0.64; 95% CI, 0.40-1.03; P = .06; PFS HR, 0.79; 95% CI, 0.54-1.15; P = .22; ORR, 53.8% vs 44.6%). Safety was as expected for onartuzumab. CONCLUSIONS AND RELEVANCE: Addition of onartuzumab to first-line mFOLFOX6 did not significantly improve clinical benefits in the ITT or MET 2+/3+ populations. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT01662869